Preparing Preservice Teachers for Inclusive Classrooms: A State-Wide Survey of Teacher Education Faculty - Lang, Lucinda Anne; Bell, Sherry Mee (Journal of the American Academy of Special Education Professionals, 2017)
Faculty (N = 154) from approved Tennessee teacher education programs across the range of disciplines responded to an online survey designed to assess the extent to which they practice, teach, and express confidence in co-teaching, collaboration and implementation of universal design for learning (UDL). Faculty strongly endorsed items indicating they practice, teach, have confidence in, and receive departmental support for collaboration and UDL. In contrast, faculty less strongly endorsed items on their practice, teaching, confidence, and departmental support for co-teaching. General education faculty reported less practice of (p < 0.01) and confidence in (p < 0.01) co-teaching than special education faculty. From open-ended responses, major obstacles identified were lack of time, separation of general and special education departments, "buy-in", and lack of skill in and knowledge of those practices. Results confirm the need for cross-discipline collaboration between general and special teacher education faculty to ensure candidate preparation for effective inclusive practice.